Atom probe revels the structure of InxGe1-xN based quantum wells in three dimensions - Galtrey, M; Oliver, R; Kappers, M; McAleese, C; Zhu, D; Humphreys, C; Clifton, P; Larsen, D; Cerezo, A (2008)
The three-dimensional atom probe has been used to characterize InxGa1-xN based multiple quantum well structures emitting from the green to the ultra-violet with sub-nanometre resolution over a 100 nm field of view. The results show gross discontinuities and compositional variations within the UV-emitting quantum well layers on a 20-100 nm length scale. We propose that these may contribute to the high efficiency of this structure: In addition, the analysis shows the presence of indium in the barrier layers of all the samples, whether or not there was an indium precursor present during barrier growth. The distribution of indium within the blue- and green-emitting InxGa1-xN quantum wells is also analyzed, and we find no evidence that InxGa1-xN with a range of compositions is not a random alloy, and so rule out indium clustering as the cause of the reported carrier localization in these structures. The upper interface of each quantum well layer is shown to be rougher and more diffuse than the lower. and the existence of monolayer steps in the interfaces that could effectively localize carriers at room temperature is revealed. (C) 2008 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.